Implementasi Metode Bermain APE (Alat Permainan Edukatif) untuk Meningkatkan Kemampuan Kognitif Anak Kelas B di PAUD Cahaya Kasih Bengkayang - Agustina, Merry; Hosan, Hosan (Jurnal Maitreyawira, 2026)
This research aims to determine the increase in cognitive abilities, especially in recognizing the concept of numbers after applying the ETA (Educational Teaching Aid) playing method. This type of research is classroom action research. The subjects of this research were 18 students in class B2 odd semester at PAUD Cahaya Kasih Bengkayang. Research data on improving cognitive abilities, especially recognizing the concept of numbers, was collected using the observation method. The data that has been collected is analyzed by tabulating the assessment, calculating the percentage of program achievement and comparing it with the achievement indicators for each cycle. In the pre-cycle, the average cognitive ability, especially in recognizing the concept of numbers, in Cahaya Kasih Bengkayang PAUD class B2 children was 16.6%. Then the data results showed that there was an increase in the average cognitive ability, especially in recognizing the concept of numbers in class B2 children at PAUD Cahaya Kasih Bengkayang after implementing the ETA learning method in cycle I by 61.1%, in cycle II it was 83.3%, then in cycle III becomes 100%. The increase in children's cognitive abilities, especially recognizing the concept of numbers, after implementing the ETA learning model was 83.4%. This shows that the application of the ETA method can improve children's cognitive abilities, especially in recognizing the concept of numbers in class B2 odd semester children at Cahaya Kasih PAUD Bengkayang.